Adequacy of molar distalization after second and third molar eruption- a case report - Babu Balina, Sarath; Harsha G V, Durga; C V, Padmapriya; DPK, Varma; C V, Goutham (International Journal of Dental Research, 2018)
Adult patients with class II malocclusion can be treated routinely by extraction therapy. In the recent decades there was increasing popularity towards non-extraction treatment. Distalization of maxillary molars is one of the prime treatment modality to correct mild to moderate class II malocclusion cases with esthetically acceptable profile. A 16 years old female patient reported with irregularly placed upper front teeth and was diagnosed as Angleâ€™s Class II malocclusion with orthognathic maxilla and mandible, average growth pattern. Treatment was planned to distalize the entire maxillary arch using mini implants as skeletal anchorage. 4.0 mm of maxillary molars were distalized, class I molar and canine relation were achieved bilaterally within span of 10 months without altering the patientâ€™s existing profile.Â Â